The relationship between anxiety and psychological distress with adherence to treatment in people with overweight after surgery - Rafieipoo, Atusa; Kooshki, Shirin (International Journal of Applied Behavioral Sciences, 2022)
Background and Aim:One of the main concerns of health psychology is the follow-up of patients regarding to treatment adherence. Anxiety related to weight and psychological distress are the factors that play important roles in people with overweight after surgery. The present study aimed to investigate the relationship between anxiety and psychological distress with adherence to treatment in people with overweight after surgery. Materials and Methods:The research method utilized in this study was descriptive correlational. The statistical population included all obese patients who had undergone sleeve gastrectomy surgery at the Endocrine and Metabolism Research Center. 147 of them were selected by available sampling method. Research instruments included Beck Anxiety Inventory, Kessler Psychological Distress Scale and General Adherence Scale. Data were analyzed using structural equation modeling method. Results:The results of this study demonstrated that anxiety and psychological distress are related to adherence to treatment among women with overweight after surgery(p≤0/05). Further, the regression analysis suggested that anxiety and psychological distress predict, respectively, 54% and 58% of the variance of changes in treatment adherence. Conclusion:It can be stated that targeting psychological constructs such as anxiety and psychological distress during treatment process can be an effective way to enhance treatment adherence among people